Uptake of universal health coverage provided, maternal, neonatal and child health services, in Machakos County Kenya - Kangee, Maureen; Mwanzo, Isaac; Oyore , John Paul (International Journal Of Community Medicine And Public Health, 2023)
Background: The Universal Health Coverage (UHC) offers an essential package of health services to citizens while protecting them financially in case of an illness. It has been given a top priority globally as a health-related aim. In Kenya, whereas MNCH services have continued to attract investment over the years, reports still show high rates of maternal and child mortality. The study sought to assess the level of uptake of universal health coverage provided MNCH services and the associated factors. Methods: This was a cross-sectional study undertaken in 422 households in Machakos Sub-County on women of reproductive age (WRA). The data was collected using questionnaires. Multiple logistic regression with (p<0.05) at 95% CI was used for inferential statistics. Results: The results show that all respondents had sought at least one MNCH service. Time taken to reach a health facility (OR 12.26; 95% CI 1.07 to 140.48) and feeling that a CHV could attend to them during an emergency (OR 4.14; 95% CI 1.23 to 13.91) were significant patient related factors. Supply side factors found to be significant were visit from a CHV (OR 125.93; 95% CI 18.37 to 863.27), feeling that services were of quality (OR 684.411; 95% CI 50.65 to 9248.93, adequacy of staff (OR 1.00; 95% CI 1.0004 to 0.021 and hospital commodities (OR 19.83; 95% CI 1.67 to 235.93). Demographic factors established to be significant were marital status, education level, occupation and monthly income. Conclusions: Patient-related, supply-side and demographic factors had a significant influence on uptake of UHC provided MNCH services.